(untitled) (International Journal of Mathematics and Physics, 2019)
As the earliest period of breast cancer, the ductal carcinoma in situ (DCIS) model has wide applications in the diagnosis of breast cancer and has been attracted much attention in recent years. In this paper, a novel PSO method is developed for solving an inverse problem of the DCIS model from nonlocal and terminal data. The numerical simulations show that the proposed method is efficient, accurate, robust against noise and fast. Moreover, it is better than the optimization method in the literature [8].